Spring Data ji shu shou ce = Spring Data : modern data access for enterprise Java / = Spring Data : modern data access for enterprise Java - Pollack, Mark; Gierke, Oliver; Risberg, Thomas; Brisbin, Jon; Hunger, Michael (GoTop Information, Inc., 2013)
Detailed summary in vernacular field.
Includes bibliographical references and index
Keywords: Java (Computer program language); Application software -- Development; Database management; Java (Langage de programmation); Logiciels d'application; Développement; Bases de données; Gestion; Application software; Development